Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2019)
TRB Special Report 329: Renewing the National Commitment to the Interstate Highway System: A Foundation for the Future explores pending and future federal investment and policy decisions concerning the federal Interstate Highway System. Congress asked the committee to make recommendations on the 201cfeatures, standards, capacity needs, application of technologies, and intergovernmental roles to upgrade the Interstate System201d and to advise on any changes in law and resources required to further the recommended actions. The report of the study committee suggests a path forward to meet the growing and shifting demands of the 21st century.The prospect of an aging and worn Interstate System that operates unreliably is concerning in the face of a vehicle fleet that continues to transform as the 21st century progresses and the vulnerabilities due to climate change place new demands on the country2019s transportation infrastructure. Recent combined state and federal capital spending on the Interstates has been about 20201325 billion per year. The estimates in this study suggest this level of spending is too low and that 45201370 billion annually over the next 20 years will be needed to undertake the long-deferred rebuilding of pavements and bridges and to accommodate and manage growing user demand. This estimated investment is incomplete because it omits the spending that will be required to meet other challenges such as boosting the system2019s resilience and expanding its geographic coverage.The committee recommends that Congress legislate an Interstate Highway System Renewal and Modernization Program (RAMP). This program should focus on reconstructing deteriorated pavements, including their foundations, and bridge infrastructure; adding physical capacity and operations and demand management capabilities where needed; and increasing the system2019s resilience. The report explores ways to pay for this program, including lifting the ban on tolling of existing general-purpose Interstate highways and increasing the federal fuel tax to a level commensurate with the federal share of the required RAMP investment.View the videos, recorded webcast, graphics, summary booklet, press release, and highlights page at interstate.trb.org.

Best-Value Procurement Methods for Highway Construction Projects - Transportation Research Board; National Academies of Sciences, Engineering,; Medicine (The National Academies Press, 2006)
TRB2019s National Cooperative Highway Research Program (NCHRP) Report 561: Best-Value Procurement Methods for Highway Construction Projects examines procurement methods, award algorithms, and rating systems for use in awarding best-value highway construction contracts. The report also explores screening criteria for selecting projects for application of best-value procurement, implementation strategies, and a model best-value specification.